Is Y-2(B12H12)(3) the main intermediate in the decomposition process of Y(BH4)(3)? - Yan, Yigang; Remhof, Arndt; Rentsch, Daniel; Lee, Young-Su; Cho, Young Whan; Zuettel, Andreas (ROYAL SOC CHEMISTRY, 2013)
Dodecaborates, i.e. the [B12H12](2-) containing species, are often observed as main intermediates in the hydrogen sorption cycle of metal borohydrides, hindering rehydrogenation. In the decomposition process of Y(BH4)(3), yttrium octahydrotriborate, i.e. Y(B3H8)(3), rather than the stable Y-2(B12H12)(3), is formed as the main intermediate.
Keywords: HYDROGEN STORAGE; POLYHEDRAL BORANES; METAL BOROHYDRIDES; REVERSIBILITY; LIBH4